The Implementation of Digital Accounting and Its Impact on Business Performance at the Bayan District MSME Forum - Tri Nurjanah; Nur Siyami; Rusmiyatun Rusmiyatun (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of the implementation of an integrated digital accounting system on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Bayan District. Design/Methodology/Approach: This study uses a quantitative approach, data is collected through a structured questionnaire distributed to 75 MSME actors. The data analysis techniques used include validity and reliability tests, simple correlation tests, simple linear regression, determination tests and t. The results of the study show that the application of digital accounting systems has a positive and significant effect on business performance Information quality is not able to mediate the relationship between the influence of digital accounting use on business performance in MSME actors. The results of this study empirically conclude that the use of digital accounting has a positive and significant effect on business performance in MSME actors, which means that the better the use of digital accounting carried out by MSME actors, the more likely it is to improve business performance in MSMEs.